2021
DOI: 10.4149/bll_2021_004
|View full text |Cite
|
Sign up to set email alerts
|

Neurological symptoms in COVID-19 patients

Abstract: OBJECTIVES: Our study aimed to investigate neurological symptoms in patients with COVID-19 and contribute to this area of limited knowledge. BACKGROUND: Increasing evidence shows that neurotropism is a common feature of Coronaviruses (CoVs). Like the other CoVs, SARS-CoV 2 uses angiotensin-converting enzyme 2 (ACE2). The brain is thought to express ACE2 receptors detected on glial cells and neurons. There are also ACE2 receptors in skeletal muscles. Our study aimed to investigate neurological symptoms in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…suggested to serve as an alternative pathway for viral entry into the CNS. 7,8 During COVID-19 infections, chemosensory symptoms, such as olfactory dysfunction (OD), may occur as a form of viral prodroma or may present concurrently with the development of other disease symptoms. 9 Anosmia or hyposmia, often accompanied by changes in taste, is now recognized as a common symptom that can assist in the diagnosis of COVID-19.…”
mentioning
confidence: 99%
“…suggested to serve as an alternative pathway for viral entry into the CNS. 7,8 During COVID-19 infections, chemosensory symptoms, such as olfactory dysfunction (OD), may occur as a form of viral prodroma or may present concurrently with the development of other disease symptoms. 9 Anosmia or hyposmia, often accompanied by changes in taste, is now recognized as a common symptom that can assist in the diagnosis of COVID-19.…”
mentioning
confidence: 99%
“…It is unlikely that all olfactory neurons will die immediately after COVID-19 infection in every infected individual. As illustrated by Altunisik et al, 28 a small number of infected individuals suffer from complete anosmia. Butowt and von Bartheld 29 determined a significant difference in the prevalence of loss of smell in patients in different populations.…”
Section: Discussionmentioning
confidence: 90%
“…A recent study has described the expression of ACE2 receptors on glial cells neurons and skeletal muscle cells. 28 The authors also reported several post-COVID-19 manifestations, including neurological symptoms in 31.37% of patients (the most common neurological symptom was headache in ~20% of the patients).…”
Section: Discussionmentioning
confidence: 94%
“…It should be considered that cancer patients may also experience tiredness as accompanying symptoms of the underlying disease and oncological treatment [26]. Altunisik et al showed that COVID-19 patients may have mucle injury [27]. In this regard, muscle injury may cause muscle fatigue.…”
Section: Discussionmentioning
confidence: 99%